Cybervictimization and Student Engagement in High School Students from Private Schools in Lima - Fachin Ramos, Kevin Rogers (2024)
In this study, a non-experimental, cross-sectional design with a descriptive-correlational scope was used to examine the relationship between cyber victimization and school engagement. There were 391 students who participated, 51.7% male and 48.3% female, aged 13 to 18 years (M=15.3, SD=0.895), from third (24.5%), fourth (38.8%), and fifth (36.5%) grades of secondary school from three private schools in Lima. For data collection, the School Cybervictimization Scale (ECE) and the School Involvement Scale (EIE-A) were applied. Among the results, high levels of cyberbullying victimization were found in 16% and very high levels in 21.7% of students, as well as low levels of school engagement in 20.5% and very low levels in 19.4% of students. Likewise, a statistically significant and inverse relationship was found, with a small effect size, between the variables (p <.01, rs = -.18, r2 = .03). In addition, student engagement showed statistically significant and inverse correlations, with small effect sizes, regarding the dimensions of cyber victimization: harassment (p < .05, rs = -.19, r2 = .036), invasion of privacy (p < .05, rs = -.15, r2 = .022), and denigration (p < .05, rs = -.12, r2 = .014). Similarly, cybervictimization showed statistically significant and inverse correlations, with small effect sizes, regarding the dimensions of school involvement: behavioral (p < .05, rs = -.15, r2 = .022), emotional (p < .05, rs = -.10, r2 = .010), and cognitive (p < .05, rs = -.15, r2 = .022). In summary, cybervictimization is inversely related to student engagement.